THE EFFECT OF STORAGE LENGTH ON THE PATHOGENICITY OF EIMERIA TENELLA OOCYSTS - Eryl Sri Rohayati (Jurnal Sain Veteriner, 1999)
A research has been conducted to evaluate storage length effect on the pathogeniclty of E. tenella oocysts in broiler chickens.Two groups consist eight day old chickens, four chickens in group I and four chichkens in group II were used in this research. At the age of seventeen days, all the chickens in both groups were infected with 20,000 E. tenella oocysts. Group I was infected with Eimeria tenella oocyst that had been stored for 107 days at 4°C in the refrigerator and group II was infected with E. tenella oocysts that had been stored for two days at room temperature.The data collected were the caeca lesion score and the histopathology of the caeca. Of all chichkens in both groups that were killed on the fifth days after infection.The data of the caeca lesion score was analysed using the Rank test (Ferguson and Takane, 1989) while the data of caeca histopathology was analyzed descriptively.The result of the research on the caeca lesion score showed that there was a significant difference between group I and group II (P < 0,01). In group I the caeca lesion score was relative light (0) - (+1) if compared with group two (+4). The result of the research on the caeca histopathology showed that in group I the histopathological changes were relative light if compared with group II. In group II there was a great inflamation reaction and the coccidia stadia varied greatly.The conclusion of the research was when oocysts storage for 107 days will be influence the pathogenicity of the E. tenel1 a oocyst s.